EVALUATION OF DRUG USE IN PATIENTS PREOPERATIVE AT CENTRAL SURGERYCAL INSTALLATION RSUD dr. SOEKARDJO TASIKMALAYA - Retnasari, Irma (STIKes Bakti Tunas Husada, 2018)
Surgical services are hospital services which often lead to medical injuries and complications such as wound infection (ILO) and anesthetic complications are becoming one of the most common causes of serious surgical complications. Provision of appropriate drug therapy, safe, effective and patient safety standards and monitoring operations can be reduces the incidence of complications and mortality of patients. The use of appropriate drug therapy, safe and effective can be determined by evaluation of the use of drugs. This study aims to describe the pattern of drug use and appropriateness of using the drug in patients in the preoperative surgical installation of central dr. Soekardjo Tasikmalaya which include proper indications, the exact dosage and drug interactions. This study is a cross-sectional, Data collection was done prospectively and statistical data. Data generated from the 120 patients who met the inclusion criteria preoperative inaccuracy indications showed 22.5%; inaccuracy dose of 22.9% and 87.5% of potential drug interactions.Â Keywords: preoperative, drug use evaluation, Antibiotic prophylaxis, anesthesia.